Thinking inside the box: intracellular roles for complement system proteins come into focus - O’Brien, RM; Lynam-Lennon, N; Olcina, MM (Springer Nature, 2023)
Over the last decade, perspectives on the complement system in the context of cancer have shifted, with complement proteins now implicated in many of the hallmarks of cancer. Systemically, the generation of complement anaphylatoxin C5a, the most potent inflammatory mediator of the cascade, occurs following convertase-mediated cleavage of complement component C5. In a recent manuscript, Ding et al., propose that in colorectal cancer cells, C5 cleavage can occur intracellularly and in a convertase-independent manner, identifying cathepsin D as an enzyme capable of cleaving C5 into C5a [1]. Intracellular C5a is functional and promotes β-catenin stabilisation via the assembly of a KCTD5/cullin3/Roc-1 complex. Importantly, the blockade of C5aR1 prevents tumorigenesis. This study adds to a growing body of evidence indicating that complement proteins, previously thought to primarily have extracellular or membrane-bound functions, also have important intracellular roles.